2010
DOI: 10.1177/0886260510388289
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Impulsivity, Trait Anger, and the Perpetration of Intimate Partner and General Violence Among Women Arrested for Domestic Violence

Abstract: The problem of domestic violence is widespread, with research indicating men and women both perpetrate a substantial amount of aggression. However, aggression perpetrated by women is a relatively understudied area compared to aggression perpetrated by men. Additionally, research is needed to determine the correlates of aggression perpetration among women, as this can inform more effective treatment programs. Thus, the current study sought to examine the association between trait anger and impulsivity and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 39 publications
10
76
1
2
Order By: Relevance
“…In a study of domestic violence offenders, 29.4 % of men and 33.3 % of women had clinically significant levels of APD (Simmons et al 2005). Although there are fewer studies that have examined APD-physical partner violence associations among women, research has found that a history of early aggression (Mauricio et al 2007) and anger and impulsivity (Shorey et al 2011) is also associated with women's perpetration of physical partner violence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study of domestic violence offenders, 29.4 % of men and 33.3 % of women had clinically significant levels of APD (Simmons et al 2005). Although there are fewer studies that have examined APD-physical partner violence associations among women, research has found that a history of early aggression (Mauricio et al 2007) and anger and impulsivity (Shorey et al 2011) is also associated with women's perpetration of physical partner violence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another possibility is that emotion regulation is not as strongly associated with violence in a college sample as in a clinical sample. For example, group differences in emotion dysregulation between perpetrators and non-perpetrators of dating violence are inconsistent (Gratz & Roemer, 2004;Shorey et al, 2011). A third (admittedly post hoc) possible explanation is violence is most normative in adolescence and young adulthood (Halpern et al, 2001), thus general emotion regulation deficits are not as influential in the transition from high anger to violence, rather impulsivity is more integral to this process.…”
Section: Discussionmentioning
confidence: 99%
“…Both suicidal and violent behavior have been associated with impulsivity (Anestis, Selby, & Joiner, 2007;Mann et al, 2009;Shorey, Brasfield, Febres, & Stuart, 2011); however, specific facets of impulsivity may be more relevant to emotion dysregulation. Negative and positive urgency refer to rash behavior in response to negative and positive emotional experiences, respectively (Cyders et al, 2007;Whiteside & Lynam, 2001), and may facilitate risk behavior in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Because some studies have found an inverse relationship between education level and IPV (e.g., Cunradi, 2007;Sorenson et al, 1996), a more highly educated sample might show lower rates of IPV, thus making it somewhat less likely that we would be able to detect associations between IPV and our predictors of interest. Finally, no data were collected on a number of potential confounders of the associations under study, including level of anger, hostility, and psychological aggression (Frye and Karney, 2006;Schumacher et al, 2008;Shorey et al, 2011).…”
Section: Discussionmentioning
confidence: 99%